Method for the Analysis of 7 Indictor Polychlorinated Biphenyls (PCBs) and 13 Organochlorine Pesticide Residues in Sediment by Gas Chromatography (GC). Issue 2 (February 2019) - Tian, Liangliang; Huang, Dongmei; Shi, Yongfu; Han, Feng; Wang, Yuan; Ye, Hongli; Tang, Yunyu; Yu, Huijuan
Abstract: This study described the development of a multiresidue method based on gas chromatography (GC) for the detection of 7 indictor polychlorinated biphenyls (PCBs) and 13 organochlorine pesticide (OCPs) residues in sediment with electron capture detector (ECD). The samples were extracted by n-hexane/dichloromethane (1/1, v/v) by ultrasonic extraction. The extracts were desulfurization with copper powder and purification with concentrated sulfuric acid. The method was validated by the analysis of spiked Tai lake sediment. Analytical performances were evaluated in terms of linearity, quantification limits, accuracy, and precision. Good linearity responses with coefficients of determination higher than 0.9945 were obtained. Methodological limit of quantitation (LOQ) was 0.5-5.0μg/kg for OCPs and PCBs. The recovery and RSDs of three-level spiked samples were in the ranges of 71.6%-105% and 3.2-11.2%. This method is highly effective to reduce the cost and time for the pretreatment of sample, and offers the ability to detect and quantify the PCBs and OCPs in sediments.